Treating Obesity with Personalized Cognitive Behavioral Therapy - Dalle Grave, Riccardo (Springer International Publishing, 2018)
This book describes a novel therapy for obesity that associates the traditional procedures of weight-loss lifestyle modification with specific, individualized cognitive behavioral procedures to address some obstacles that have been indicated by recent research to influence weight loss and maintenance. The Cognitive Behavioral Therapy for Obesity (CBT-OB) can be used to treat all classes of obesity, including patients with severe comorbidities and disability associated with obesity, who are not usually included in traditional weight-loss lifestyle modification treatments. The book describes the treatment program in detail, and with numerous clinical vignettes. It also discusses involving significant others in the change process and adapting the CBT-OB for patients with severe obesity, binge-eating disorder, medical and psychiatric comorbidity, and treated with weight-loss drugs or bariatric surgery. Lastly, a chapter is dedicated to the use of digital technology with CBT-OB in order to help patients monitor their food intake and physical activity and to addressing obstacles in real time. Thanks to the description of how to apply the latest, evidence-based CBT-OB to real world settings, this volume is a valuable useful tool for all specialists - endocrinologists, nutritionists, dietitians, psychologists, psychiatrists - who deal with obesity and eating disorders.